Strategic Optimization of Website Performance through AI, Multi-Channel Integration, And CRM: An Impact Analysis on Customer Conversion, Customer Loyalty, and Business Economic Performance at Pt. XYZ - Kartadinata, Hansel Christianto; Sutjipto, Dr. M. Riza (International Journal of Scientific Research and Management (IJSRM), 2025)
The enhancement of customer conversion rate and the improvement of PT. XYZ’s economic performance are critical for reinforcing the company’s position in among digital marketplace. PT. XYZ faces substantial challenges in evaluating the effects of Customer Relationship Management implementation, AI-based website optimization, and multi-channel integration on customer satisfaction, engagement, and loyalty. This study aims to assess the influence and interrelation of CRM practices on customer conversion through customer satisfaction, determine the impact of AI-driven website optimization by analyzing engagement rates, also explores the role of multi-channel integration in fostering customer loyalty, considering customer retention metrics. The study also explores the role of multi-channel integration in fostering customer loyalty, considering customer retention metrics. Data was obtained by questionnaire from 100 active users of PT. XYZ Website. Statistical analyses, including tests for validity, reliability, normality, correlation, and paired t-tests, were employed to examine the relationships between variables. The results indicate that CRM implementation positively and significantly affects customer conversion in a linear manner, mediated by customer satisfaction. AI-based website optimization demonstrates a positive and significant nonlinear effect on economic performance, as reflected by engagement rates. Although the impact of multi-channel integration was not statistically significant. So, it is recommended that PT. XYZ pursue an integrated approach by combining CRM, AI-enhanced website optimization, and multi-channel strategies to improve customer conversion, loyalty, and overall economic performance. The insights derived from this study provide valuable guidance to improve the innovativenest and effectivenest digital marketing strategies.